2017
DOI: 10.2147/dmso.s148392
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and brain illness: from cognitive and psychological evidences to obesity paradox

Abstract: Recent findings showed that obesity represents an additional risk factor to developing brain illness such as cognitive impairments and psychopathological disorders. However, some benefits of overweight in the elderly have been identified and an “obesity paradox” has been shown. Currently, it is still unknown how obesity and brain functioning could be linked, and the process by which body fat independently injures cognitive abilities and psychological well-being remains unclear. To establish the independent rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 110 publications
2
39
0
3
Order By: Relevance
“…For instance, a recent analysis of the Whitehall II study of > 10,000 individuals in the UK found obesity at age 50 but not at age 60 or 70 predicted dementia risk [56]. Some studies even corroborate an “obesity paradox” with beneficial effects of obesity on cognitive function in later life [57] which may reflect effects of prodromal stages of dementia on body weight [56, 58]. We have no information on body weight status at midlife or weight trajectories of participants but suspect that similar processes may underlie the lack of an association of obesity and POCD risk in the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent analysis of the Whitehall II study of > 10,000 individuals in the UK found obesity at age 50 but not at age 60 or 70 predicted dementia risk [56]. Some studies even corroborate an “obesity paradox” with beneficial effects of obesity on cognitive function in later life [57] which may reflect effects of prodromal stages of dementia on body weight [56, 58]. We have no information on body weight status at midlife or weight trajectories of participants but suspect that similar processes may underlie the lack of an association of obesity and POCD risk in the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PA is usually considered very important in many chronic diseases, reducing morbidity and mortality (Blair et al, 1989;Lee et al, 2012;Messina et al, 2017b;Polito et al, 2018;Sessa et al, 2018b). Several studies have described a positive outcome for those asthma patients who combined biologic therapy with PA: a positive correlation has been described between PA levels and lung function in asthma patients (Ritz et al, 2010;Monda et al, 2017a;Panico et al, 2017;Vanacore et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity can bring about the reduced volume of the brain and related diseases by declining neurogenic function, as well as increased neuronal death, oxidative stress and inflammation (3). Studies show that an increase in each unit of BMI, which is a benchmark for obesity, is associated with a decrease of 0.5% to 1.5% in the brain tissue and an increase in the atrophy of the hippocampus (4). Many studies have confirmed the relationship between obesity and reduced brain volume and consequently, mental disorders (3).…”
Section: Introductionmentioning
confidence: 99%